Creation of programs for controlling programmable logic controllers using universal development tools - Farit I. Lotfullin; Marat R. Khamidullin; Gulnara A. Gareeva (International Journal of Advanced Studies, 2025)
Background. Programmable logic controllers (PLCs) play a key role in automation systems across a variety of industries, including industrial manufacturing, transportation, and the energy sector. However, specialized development environments offered by PLC manufacturers often have limited compatibility, tying users to specific hardware and creating additional training and development costs. This has stimulated interest in more universal approaches using open standards and tools.